2017
DOI: 10.1111/mcn.12461
|View full text |Cite
|
Sign up to set email alerts
|

Local foods can meet micronutrient needs for women in urban Burkina Faso, but only if rarely consumed micronutrient‐dense foods are included in daily diets: A linear programming exercise

Abstract: Women of reproductive age are at nutritional risk due to their need for nutrient-dense diets. Risk is further elevated in resource-poor environments. In one such environment, we evaluated feasibility of meeting micronutrient needs of women of reproductive age using local foods alone or using local foods and supplements, while minimizing cost. Based on dietary recall data from Ouagadougou, we used linear programming to identify the lowest cost options for meeting 10 micronutrient intake recommendations, while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Among the animal foods, meat, dairy, eggs and anchovy are the richest sources of micronutrients. In plant foods, the highest levels of micronutrients are found in seeds/nuts, dark leafy vegetables and vitamin A and C-rich fruits (18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the animal foods, meat, dairy, eggs and anchovy are the richest sources of micronutrients. In plant foods, the highest levels of micronutrients are found in seeds/nuts, dark leafy vegetables and vitamin A and C-rich fruits (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Foodbased approaches may be the preferred strategy because they are more sustainable, economically feasible and culturally acceptable and can be used to alleviate several micronutrient deficiencies simultaneously, without inducing antagonistic micronutrient interactions (21) . However, there are limitations with the effectiveness of food-based interventions, especially when the diets are inadequate in nutrients (18,20) , also because most nutrients might be wasted through limited absorption in the gut (20,21) . There is thus a need for more sustainable and low-cost community-based nutrition interventions, especially those utilising nutrient-dense foods that are locally produced.…”
mentioning
confidence: 99%
“…In addition, it identifies nutrients that are likely to remain low in diets based only on local foods (i.e., problem nutrients). LP has been used to identify problem nutrients and formulate FBRs, for young children and women of reproductive age, in geographically limited areas of Asian and African countries (Arimond, Vitta, Martin-Prével, Moursi, & Dewey, 2017) (Raymond, Kassim, Rose, & Agaba, 2017) (Fahmida, Santika, Kolopaking, & Ferguson, 2014) (Hlaing et al, 2016) (Hlaing et al, 2016) (Hlaing et al, 2016) (Ferguson, Chege, Kimiywe, Wiesmann, & Hotz, 2015) (Santika, Fahmida, & Ferguson, 2009). This study will be the first to make intercountry comparisons, using nationally representative datasets for women of reproductive age and young children.…”
Section: Introductionmentioning
confidence: 99%
“…Termote et al (24) also revealed a lack of iron, zinc, calcium, vitamin B 6 in CoD modeled diets in Baringo, Kenya. In a study done by Arimond et al (43) in Burkina Faso, the authors indicated that recommended intakes for iron, vitamin B 2, B 6 , and B 12 , folate and calcium are difficult to achieve through local food sources. This implies that iron is a primary missing nutrient in diets across countries.…”
Section: Discussionmentioning
confidence: 99%